Discerning the Influence of Total Body Weight and Pregnancy on the Contribution to Heat Balance - Dervis, Sheila (Université d'Ottawa / University of Ottawa, 2021)
Evidence-based Canadian physical activity guidelines established specifically for pregnant women have shown to improve maternal and fetal outcomes, including prevention of adversities such as excess gestational weight gain, preeclampsia, and gestational diabetes. Unfortunately, most pregnant women fail to meet recommended guidelines for physical activity, and in many circumstances, the prevailing motive is due to a fear of overexertion and overheating harming the fetus. These concerns stem from reports of teratogenesis related to hyperthermia in several animal studies resulting in congenital fetal malformations. Although, due to disparities in thermoregulation between humans and animals, the findings are not entirely applicable to pregnant women. During exercise, the heat produced requires a given source of heat loss (i.e., skin blood flow/sweating) to maintain thermal homeostasis and a stable core temperature, preventing a continual rise in core temperature (i.e., teratogenesis). This thesis aims to separate the influence of pregnancy and body weight on oxygen consumption, heat production, heart rate, and rating of perceived exertion at rest (Study 1) and then during exercise (Study 2). On the other side of the heat balance equation is heat loss mechanisms; currently, the limited existing literature suggests that dry and evaporative heat loss increases as pregnancy progresses. Unfortunately, these findings are also based almost exclusively on animal studies. There has not been an established understanding of physiological, perceptual/behavioural responses in heat loss in pregnant women from early to late pregnancy, and the final study in this thesis sought to map the current literature in the format of a scoping review (Study 3). The findings of this thesis provide evidence that physiological measurements of oxygen consumption, heat production and heart rate are not influenced by stage of pregnancy, the responses increases/decrease according to total body mass. Additionally, both dry and evaporative heat loss responses appear to increase from early to late pregnancy.
Keywords: Thermoregulation; Pregnancy; Exercise